A brief History and Theology of the Sacrament of Reconciliation: A Study with References to the Seal of Confession - Tirimanna, Vimal (Periodica de re canonica, 2020)
The Sacrament of Reconciliation has had a very complex and non-linear development both in its history and theology. This article highlights some of the more important turning points in its process of development. In view of the Seminar at which this paper was presented, the writer has made a special effort to refer to the development of the concept of the Seal of Confession along with that of the sacrament itself. All throughout the Tradition, this Seal has been considered absolutely inviolable.